Oxygen Saturation on Admission Is a Predictive Biomarker for PD-L1 Expression on Circulating Monocytes and Impaired Immune Response in Patients With Sepsis - Avendaño-Ortiz, José; Maroun-Eid, Charbel; Martín-Quirós, Alejandro; Lozano-Rodríguez, Roberto; Llanos-González, Emilio; Toledano, Víctor; Gómez-Campelo, Paloma; Montalbán-Hernández, Karla; Carballo-Cardona, César; Aguirre, Luis A.; López-Collazo, Eduardo (Frontiers in Immunology, 2018)
Sepsis is a pathology in which patients suffer from a proinflammatory response and a dysregulated immune response, including T cell exhaustion. A number of therapeutic strategies to treat human sepsis, which are different from antimicrobial and fluid resuscitation treatments, have failed in clinical trials, and solid biomarkers for sepsis are still lacking. Herein, we classified 85 patients with sepsis into two groups according to their blood oxygen saturation (SaO2): group I (SaO2 ≤92%, n=42) and group II (SaO2 >92%, n=43). Blood samples were taken before any treatment, and the immune response after ex vivo LPS challenge was analysed, as well as basal expression of PD-L1 on monocytes and levels of sPD-L1 in sera. The patients were followed up for one month.Taking into account reinfection and exitus frequency, a significantly poorer evolution was observed in patients from group I. The analysis of HLA-DR expression on monocytes, T cell proliferation and cytokine profile after ex vivo LPS stimulation confirmed an impaired immune response in group I. In addition, these patients showed both, high levels of PD-L1 on monocytes and sPD-L1 in serum, resulting in a down-regulation of the adaptive response. A blocking assay using an anti-PD-1 antibody reverted the impaired response. Our data indicated that SaO2 levels on admission have emerged as a potential signature for immune status, including PD-L1 expression. An anti-PD-1 therapy could restore the T cell response in hypoxemic sepsis patients with SaO2 ≤92% and high PD-L1 levels.